Investigating Students' Perceptions Of The Utilization Of Chatgpt In Improving Writing Skills: Challenges And Strategies - Amanah, Wini; Marzuki, M. Junaidi; Suherman, Andri; Maysuroh, Siti (Journal of Authentic Research, 2025)
This study discusses the challenges and strategies involved in using ChatGPT as an academic writing tool. The purpose of this study is to identify user perceptions, obstacles encountered, and strategies applied in effectively utilizing ChatGPT in the context of academic writing. This study uses a qualitative approach with data collection methods through closed questionnaires, open questionnaires, and semi-structured interviews, involving 25 participants for questionnaire completion and 3 participants for interviews. Data from closed questionnaires were analyzed using percentage calculations in Microsoft Excel, while data from open questionnaires and semi-structured interviews were analyzed using Miles and Huberman's interactive analysis model, which includes data reduction, data presentation, and conclusion drawing stages. The results showed that most respondents had a positive view of ChatGPT as an academic writing tool (S4 = 1.56; S10 = 1.64), although their proficiency level was still in the moderate category (S1 = 1.28). The main challenges identified include over-reliance on ChatGPT, which has led to a decline in independent writing skills (S5 = 1.92), the provision of irrelevant answers (S6 = 2.48), and a decline in creativity (S9 = 2.16). In addition, respondents also highlighted the inaccuracy of references and overly general answers as additional obstacles. In terms of strategy, users attempted to verify information sources, use ChatGPT only in the early stages of writing, and maintain the originality of their writing. Overall, the results of this study show that ChatGPT can be an effective tool in supporting the academic writing process when used wisely, critically, and responsibly.